COMPARATIVE ANALYSIS OF WARREN, PRATT, AND HOWE STEEL TRUSS BRIDGES (60 M SPAN) BASED ON SNI 1725:2016 - Frinsilia Jaglien Liando Frinsilia; Steenie Edward Wallah Steenie; Fabian Johanes Manoppo Fabian; Ficky Marcellino Oroh Ficky (EDUCATIONE, 2026)
The rapid development of transportation infrastructure requires bridge designs that are safe, efficient, and economical. Steel truss bridges are widely used for medium- to long-span applications due to their high strength-to-weight ratio. This study aims to analyze and compare the structural performance of Warren Truss, Pratt Truss, and Howe Truss steel bridges with a 60 m span and to determine the most optimal truss configuration based on structural performance parameters. The main contribution of this study is the integration of truss-type comparison with two seismic loading scenarios, namely locally derived seismic parameters developed from site-specific seismic hazard and soil condition data, and seismic parameters specified in SNI 2833:2016. A quantitative approach was employed through numerical structural analysis using MIDAS Civil software based on the Load and Resistance Factor Design (LRFD) method. Each bridge model was analyzed using identical geometric, material, and loading conditions. Structural performance was evaluated based on the Demand Capacity Ratio (DCR), maximum deflection, structural weight, and support reactions. Two seismic scenarios were considered, namely local seismic parameters generated using EZ-FRISK and seismic parameters based on SNI 2833:2016. The results indicate that all truss configurations satisfy the structural safety requirements with DCR values not exceeding 1.0. The Warren Truss exhibits the best overall performance, with maximum DCR values of 0.989 under local seismic loading and 0.970 under SNI seismic loading, a maximum deflection of 66.14 mm, and the lightest structural weight of 3000.8 kN. The Pratt Truss and Howe Truss have structural weights approximately 2.31% and 7.94% greater than that of the Warren Truss, respectively. The analysis further reveals that the locally derived seismic parameters generate higher internal forces, DCR values, and support reactions than those obtained from SNI 2833:2016, although their influence on structural deflection is relatively insignificant. Based on the evaluation of DCR, deflection, structural weight, and support reactions, the Warren Truss is identified as the most optimal configuration for a 60 m span steel truss bridge. This truss type provides the best balance of structural safety, stiffness, stability, and material efficiency. The findings of this study may serve as a reference for selecting steel truss configurations and highlight the importance of incorporating site-specific seismic characteristics into bridge design.